STUDI BATUAN VULKANIK PERBUKITAN SEPULUHRIBU, KOTA TASIKMALAYA DAN SEKITARNYA, JAWA BARAT - , HERNANDA DANAR DONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Ten Thousand, Hills located at Tasikmalaya City, West Java are hummocky hills feature which consist of small isolated hills with size10-100 m in diameter and 10-150 m in height. Previuos studies by some researcher, interpretated these hills to be was formed by sector collapse of Mout Galunggung which happened 4200 years ago (Bronto, 1989). However, based on new outcrops was exposed in this area reveal that some outcrops show different characteristic with sector collapse deposits. For this reason, author iis conducting research to understand the genesis of vulcanic rock in the Ten Thousand hills through detail by physic description of outcrops, petrography anlysis dan geochemichal analysis. Some outcrops consist of intrusion, scorialapili- tuf layers and autoclastica breccia, geological structure like tectonic joints, normal faults and strike slip faults whih are affected by such features shouldnât be found in sector collapse deposit. Geochemical and petrography analysis of these rock sampel compared with previous research data, suggest that mineralogy of these rocks are more basaltic. Geochemical plot diagram also show different geochemichal characters with previous research data. Based on the collected data dan laboratory analysis, litological units on Ten Thousand Hills are interpretated not only consisted by debris avalanche and lahar deposit, but also consisted by insitu vulcanic rocks which can be grouped as : Asasutra volcanic rock, Situgede volcanic rock, Rancamacan volcanic rock, Cintaraja volcanic rock and Cipasung volcanic rock. These rock are older and covered by debris avalanche and lahar deposit. They have relatively had small size and are scaterred separately, indicating product of small volcanoes or volcnism in this area. Authors interpretates that they are three location of small insitu volcano at the Ten Thousand Hills area, i.e : Asasutra volcano, Situgede Maar, and Cipasung volcano. However, Cintaraja volcanic rock and Rancamacan volcanic rock canât be interpretated the eruption center because the limited outcrops and unsupported data.